How important is practicum to pre-service teacher development for inclusive teaching? Effects on efficacy in classroom management. - Sokal, Laura; Woloshyn, Debra; Funk-Unrau, Savannah (Alberta Journal of Educational Research, 2014)
Sixty pre-service teachers were surveyed about their confidence, concerns, and efficacy for inclusive classroom teaching before and after a course on inclusive education. Some students experienced a practicum in an inclusive setting alongside the coursework, and some students did not. Both groups made significant gains in all dependent variables and their subscales from pre- to post-treatment. However, the students who experienced a practicum in an inclusive setting developed greater teacher efficacy in classroom management than those students with no practicum. Given the importance of successful classroom management to teacher retention and student success, the findings support the importance of high-quality inclusive practica as an essential feature of effective inclusive teacher preparation programs. Nous avons fait une enquête auprès de soixante enseignants avant l’emploi; les questions portaient sur leur niveau de confiance, leurs préoccupations et leur efficacité à créer une salle de classe inclusive avant et après un cours sur l’éducation inclusive. Certains étudiants ont fait un stage dans un milieu inclusif en plus de leur travail de cours, d’autres n’ont pas suivi le stage. Les deux groupes ont réalisé des progrès importants relativement à toutes les variables et leurs sous-échelles entre le pré- et le post-traitement. Toutefois, les étudiants ayant passé par le stage dans un milieu inclusif sont devenus plus efficaces dans la gestion de salle de classe que ceux n’ayant pas fait le stage. Compte tenu de l’importance d’une bonne gestion de classe dans le maintien à leur poste des enseignants et dans la réussite des élèves, les résultats de cette étude viennent appuyer le rôle d’un stage de qualité dans un milieu inclusif comme composante essentielle des programmes de formation des enseignants.